Polymer nanospheres formed by a microfluidic technique with Evans blue dye†. (26th November 2015) - Kucuk, Israfil
Abstract : In this work, the V‐shaped microfluidic junction (VMJ) device technique with gas/liquid interface was used to prepare textured polymer nanospheres from bubble bursting for drug delivery. The polymer/dye solution, N2 gas, and a volatile liquid, perfluorohexane (PFH) were simultaneously fed using the tubes into the VMJ device. A high‐pressure injection of N2 gas into the VMJ interacts with PFH and ethanol leading to the preparation of a microbubble system. Once bubbles are ejected from the VMJ outlet, nanospheres calve from the parent bubble. The collection temperature and the N2 gas pressure play a key role in the mechanism by which nanospheres are formed. In addition, the volatile liquid, PFH, is described as a significant surface modifier. The influence of the N2 gas pressure, collection temperature, and the volatile liquid flow rates on nanospheres size distribution and surface roughness were investigated using scanning electron microscopy. The results revealed that the N2 gas pressure and collection temperature are crucial in tailoring the size distribution of the nanospheres and that the nanospheres textured with PFH had significantly rougher surface. Nanospheres coated with Evans blue dye were prepared, and those collected at high temperature exhibited a very different dye release profile compared with those collected at lower temperatures. Copyright © 2015 John Wiley & Sons, Ltd.